“Fertile island” effects of Tamarix chinensis Lour. on soil N and P stoichiometry in the coastal wetland of Laizhou Bay, China - Rong, Qiangqiang; Liu, Jingtao; Cai, Yanpeng; Lu, Zhaohua; Zhao, Zhenzhen; Yue, Wencong; Xia, Jiangbao (Journal of soils and sediments, 2016)
PURPOSE: As a useful comprehensive index for reflecting nutrient cycling in soils, nitrogen (N) and phosphorus (P) stoichiometry is subject to influences of many external environmental and biological factors. Studies on such influences were limited, and the influential mechanism remains unclear. The purpose of this research is to investigate soil N and P stoichiometric variations and analyze “fertile island” effects of Tamarix chinensis Lour. (T. chinensis) in the coastal wetland of Laizhou Bay in China. MATERIALS AND METHODS: Soil samples beneath clusters and communities of T. chinensis were collected respectively in July 2012. Amounts of ammonium, nitrate, and available phosphorus in the soil samples were measured through the corresponding standard methods for material measuring. RESULTS AND DISCUSSION: In general, there were significant vertical variations in soil N and P stoichiometry beneath clusters and communities of T. chinensis. A downtrend was observed for N and P contents with the increase in soil depth. On the contrary, the N/P ratio revealed a trend of going up first and then dropping off along with the increase of the soil depth. Comparatively, the horizontal variations in the soil N and P stoichiometry beneath a single cluster of T. chinensis were greater in the topsoil than those in the subsoil. The N and P contents gradually decreased from the canopy center to the outside. On the contrary, an opposite trend was found for the N/P ratio. For the horizontal variations beneath T. chinensis communities, there were no significant differences for either N and P contents or N/P ratios. CONCLUSIONS: Similar to the ecosystems in arid and semi-arid areas, vegetations in many semi-humid areas could also form fertile islands and exert significant influences on the soil nutrient cycle. The formation of fertile islands beneath a single cluster of T. chinensis could have significant influence on soil N and P stoichiometry. Under the influence of fertile islands beneath T. chinensis, the limiting element of the biogeochemical processes in the coastal wetland of Laizhou Bay might change from N to P. However, the influences of fertile island effects on soil N and P stoichiometry beneath T. chinensis communities were relatively small, illustrating that the influences of fertile island effects was not significant at the community level. Thus, the impacts of environmental factors on soil N and P stoichiometry might be greater than that of the fertile island effects in the wetland on a larger scale.